Modelling a Linker Mix‐and‐Match Approach for Controlling the Optical Excitation Gaps and Band Alignment of Zeolitic Imidazolate Frameworks. (15th November 2016) - Grau‐Crespo, Ricardo; Aziz, Alex; Collins, Angus W.; Crespo‐Otero, Rachel; Hernández, Norge C.; Rodriguez‐Albelo, L. Marleny; Ruiz‐Salvador, A. Rabdel; Calero, Sofia; Hamad, Said
Abstract: Tuning the electronic structure of metal–organic frameworks is the key to extending their functionality to the photocatalytic conversion of absorbed gases. Herein we discuss how the band edge positions in zeolitic imidazolate frameworks (ZIFs) can be tuned by mixing different imidazole‐based linkers within the same structure. We present the band alignment for a number of known and hypothetical Zn‐based ZIFs with respect to the vacuum level. Structures with a single type of linker exhibit relatively wide band gaps; however, by mixing linkers of a low‐lying conduction edge with linkers of a high‐lying valence edge, we can predict materials with ideal band positions for visible‐light water splitting and CO2 reduction photocatalysis. By introducing copper in the tetrahedral position of the mixed‐linker ZIFs, it would be possible to increase both photo‐absorption and the electron–hole recombination times.